Generalized quadrature spatial modulation for STAR-RIS aided NOMA networks - Yonghao, Guo; Shuping, Dang; Jun, Li; Wenli, Shang; Jia, Hou; Yu, Huang (China communications, 2025)
The simultaneously transmitting and reflecting reconfigurable intelligent surface (STAR-RIS) is regarded as a promising paradigm for enhancing the connectivity and reliability of non-orthogonal multiple access (NOMA) networks. However, the transmission of STAR-RIS enhanced NOMA networks performance is severely limited due to the inter-user interference (IUI) on multi-user detections. To mitigate this drawback, we propose a generalized quadrature spatial modulation (GQSM) aided STAR-RIS in conjunction with the NOMA scheme, termed STAR-RIS-NOMA-GQSM, to improve the performance of the corresponding NGMA network. By STAR-RIS-NOMA-GQSM, the information bits for all users in transmission and reflection zones are transmitted via orthogonal signal domains to eliminate the IUI so as to greatly improve the system performance. The low-complexity detection and upper-bounded bit error rate (BER) of STAR-RIS-NOMA-GQSM are both studied to evaluate its feasibility and performance. Moreover, by further utilizing index modulation (IM), we propose an enhanced STAR-RIS-NOMA-GQSM scheme, termed E-STAR-RIS-NOMA-GQSM, to enhance the transmission rate by dynamically adjusting reflection patterns in both transmission and reflection zones. Simulation results show that the proposed original and enhanced scheme significantly outperform the conventional STAR-RIS-NOMA and also confirm the precision of the theoretical analysis of the upper-bounded BER.